Condensation pressure drop characteristics of various refrigerants in a horizontal smooth tube - Dalkilic, A. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The two-phase pressure drop characteristics of the pure refrigerants R410a, R502, and R507a during condensation inside a horizontal tube-in-tube heat exchanger were investigated to determine the two-phase friction factor, the frictional pressure drop, and the total pressure drop. The two-phase friction factor and frictional pressure drop are predicted by means of an equivalent Reynolds number model. Eckels and Pate's experimental data, presented in Choi et al.'s study provided by NIST, were used in the analysis. In their experimental setup, the horizontal test section was a 3.81 m long countercurrent flow double tube heat exchanger with refrigerant flowing in the inner smooth copper tube (8.01 mm i.d.) and cooling water flowing in the annulus (13.7 mm id.). Their test runs were performed at saturated condensing temperatures from 38.33 degrees C to 51.78 degrees C while the mass fluxes were between 119 and 617 kg m(-2) s(-1) the horizontal test section. The separated flow model was modified by ten different void fraction models and correlations, as well as six different correlations of friction factors, in order to determine the best combination for the validation of the experimental pressure drop values. Carey's friction factor was found to be the most predictive. The refrigerant side total and frictional pressure drops were determined within +/-30% using the above friction factor and the void fraction combinations of Carey, Baroczy, and Armand for R410a; and those of Carey, Spedding and Spence, and Rigot for R502 and R507a. The equivalent Reynolds number model was modified using the void fraction correlation of Rigot in order to determine the frictional condensation pressure drop and the two-phase friction factor. The effects of vapor quality and mass flux on the pressure drop are discussed in this paper. The importance of using the alternative void fraction and friction factor models and correlations for the separated flow model is also addressed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Condensation; Pressure drop; Friction factor; Void fraction; Frictional pressure drop; Separated flow; LIQUID ANNULAR-FLOW; HEAT-TRANSFER; PREDICTION; MIXTURES; FRICTION; Thermodynamics; Mechanics